Expert consensus on a train‐the‐trainer curriculum for robotic colorectal surgery. (18th May 2019) - Gómez Ruiz, M.; Alfieri, S.; Becker, T.; Bergmann, M.; Boggi, U.; Collins, J.; Figueiredo, N.; Gögenur, I.; Matzel, K.; Miskovic, D.; Parvaiz, A.; Pratschke, J.; et al.
Abstract: Aim: Robotic techniques are being increasingly used in colorectal surgery. There is, however, a lack of training opportunities and structured training programmes. Robotic surgery has specific problems and challenges for trainers and trainees. Ergonomics, specific skills and user–machine interfaces are different from those in traditional laparoscopic surgery. The aim of this study was to establish expert consensus on the requirements for a robotic train‐the‐trainer curriculum amongst robotic surgeons and trainers. Method: This is a modified Delphi‐type study involving 14 experts in robotic surgery teaching. A reiterating 19‐item questionnaire was sent out to the same group and agreement levels analysed. A consensus of 0.8 or higher was considered to be high‐level agreement. Results: Response rates were 93–100% and most items reached high levels of agreement within three rounds. Specific requirements for a robotic faculty development curriculum included maximizing dual‐console teaching, theatre team training, nontechnical skills training, patient safety, user–machine interface training and telementoring. Conclusion: A clear need for the development of a train‐the‐trainer curriculum has been identified. Further research is needed to assess feasibility, effectiveness and clinical impact of a robotic train‐the‐trainer curriculum.